Sistem Pendukung Keputusan Penerima Bantuan Rumah Tak Layak Huni (RTLH) Di Kota Binjai Dengan Metode Simplemultiple Attribute Rating Technique (SMART) (STUDI KASUS: DINAS SOSIAL BINJAI) - Yustika Indah Purwanti; Budi Serasi Ginting; Novriyenni (Yayasan Kita Menulis, 2021)
Decision support system is defined as a system that is intended to support managerial decision makers in certain situations. Decision support systems are intended to be a tool for decision makers to expand their capabilities, but not to replace their judgment. This RTLH (Unfit for Living House) assistance must be right on target for poor people who meet the criteria as requirements for receiving RTLH assistance, so that residents who are unable to receive RTLH assistance can receive the assistance. In its implementation, the underprivileged population who is entitled to receive assistance unfit for habitation is determined by the Social Service (Dinsos). One of the methods in decision support is the Simple Multi Attribute Rating Technique (SMART) method or commonly abbreviated as the SMART method. The SMART method is a method that has minimum calculations and is very simple, but objective on the results of decision support. From research conducted using the SMART method, it was found that R9 with a final optimization value of 0.725 became the recipient of uninhabitable housing assistance from 10 alternative data on uninhabitable houses analyzed.